Penerapan Model Problem Based Learning Berbantuan Geogebra untuk Meningkatkan Pemecahan Masalah pada Materi Persamaan Lingkaran - Siti Sya'diah Sulaiman Hadji; Siprianus Suban Garak; Irna Karlina Sensiana Blegur (Pendidikan Matematika FKIP Universitas Mataram, 2026)
This research is based on the low problem-solving ability of 11th-grade students at SMK Negeri 7 Kupang concerning the topic of circle equations with 27 students as research subjects. The aim of this study is to enhance these abilities by applying a Problem-Based Learning (PBL) model supported by GeoGebra. The research employs a Classroom Action Research (CAR) design according to Kemmis & McTaggart, carried out in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data were collected through observation, tests, and documentation, and then analyzed descriptively both quantitatively and qualitatively. The results of the study indicate a significant improvement in students' problem-solving skills. The average percentage of problem-solving ability in cycle I was 52.38%, which increased to 82.98% in cycle II. Improvement was also evident in each problem-solving indicator, namely: understanding the problem from 61.18% to 96.38%; making a solution plan from 40.79% to 65.79%; implementing the plan from 60.86% to 93.42%; and reviewing from 46.71% to 76.32%. Student activity also increased from 80.39% in cycle I to 100% in cycle II, while teacher activity increased from 86.67% to 100%. Thus, the application of the GeoGebra-assisted PBL model is effective in improving students' problem-solving ability in the material on circle equations.